IMPLEMENTASI PROGRAM PENCATATAN AKTA KEMATIAN DI KABUPATEN SUMEDANG - Suherman; Billy Maulana Hambali; Firma Dewi Lestari; Ihsanudin; Intan Yunita; Lulu Salsabila Nurazizah; Rena Marisa (LPPM UNSAP & FISIP UNSAP, 2023)
This study aims to examine the implementation of the death certificate program at the Population and Civil Registry Service in Sumedang district, the obstacles to its implementation, and the efforts to overcome these obstacles. The method used in preparing this research report is a qualitative research method with a descriptive type. The sampling technique used was purposive sampling, with informants: Office Secretary, Functional Position in Civil Registration, Staff 1 in Civil Registration and Staff 2 in Civil Registration. Data collection techniques through library research and field studies. In analyzing the data used the Miles and Huberman model with the steps: data reduction, data presentation, conclusion drawing/validation and triangulation. Based on the results of the study, it was concluded that the death certificate program at the Population and Civil Registration Office of Sumedang Regency is optimal if services are in the office but not optimal if services are carried out to the field. Obstacles in implementing the program include the low mindset of the people, the media used is still very simple and limited, the use of official cars is not optimal. In overcoming these obstacles, several efforts were made including employees still trying to do various ways to be able to change people's mindsets, in the process of government services trying to minimize the cost of making death certificates with brokers and no death certificates were falsified. Suggestions in implementing the program are to improve the quality of socialization, increase the equity of information distribution to all regions, improve the quality of human resources, must be able to budget for the